Examining doctorates in the creative arts : a guide. - Burr, Sandra; Brien, Donna Lee; Webb, Jen (Australasian Association of Writing Programs, 2012)
Guide produced as part of a project, 'Examination of Doctoral Degrees in Creative Arts', which investigated the assessment practices, processes and policies, as well as the beliefs and expectations of HDR (higher degree research) students, supervisors and examiners in the creative arts. Through a series of roundtables, focus groups and surveys, along with benchmarking of university policies and processes, and analysis of a body of examiners' thesis reports, the authors investigated: whether there is agreement among artist-academics about what it means to do a creative arts doctorate; how we go about the work of examining creative arts doctorates; how readily university research offices and policies accommodate creative arts practice at this level; and whether the sector can establish standards of quality.